Completed Fertility and Its Timing - Ward, Michael P.; Butz, William P. (Journal of Political Economy, 1980)
This paper presents a dynamic economic model of fertility behavior estimated with age-year-specific U.S. time-series data. The estimated model indicates that couples, on average, time their births to avoid periods when female wage rates are expected to be high, and that most of the observed effect of income and female wages on fertility rates is due to the indirect influence of these variables on couples' wage and income expectations. This paper also presents a decomposition of current fertility rates into timing and completed fertility components, allowing a comparison of current low fertility rates with couples' lifetime fertility plans. The estimates indicate that aggregate planned completed fertility is approximately equal to the fertility rate.